Whole genome sequencing as a reliable alternative for Salmonella serotyping: a comparative study with the gold-standard method - Mileto, Irene; Romano, Greta; Gaiarsa, Stefano; Grassia, Giulia; Bagnarino, Jessica; Piralla, Antonio; Monzillo, Vincenzina; Cambieri, Patrizia; Baldanti, Fausto; Corbella, Marta (Frontiers in Microbiology, 2025)
IntroductionSalmonella is a major foodborne pathogen of significant global health concern, leading to conditions like gastroenteritis, with symptoms such as diarrhea, abdominal cramps, and fever. Although most cases are self-limiting, Salmonella enterica can cause bacteremia or typhoid fever in some cases. There are over 2600 known serotypes of S. enterica. Each serotype is distinguished by differences in its surface antigens (somatic O and flagellar H), which is the basis for their classification. Considering that traditional phenotypic typing is laborious and time-consuming, the goal of this study is to evaluate whole genome sequencing for S. enterica classification.MethodsFrom January 2021 to December 2024, 282 isolates of S. enterica were collected at the Microbiology and Virology department of Fondazione IRCCS Policlinico San Matteo (Italy). The isolates were serotyped for O and H antigens with the gold-standard serum agglutination method. Whole genome sequencing. WGS was performed using Illumina MiSeq and quality-filtered reads were used to perform serotype prediction using SeqSero2 and SISTR tools.ResultsThe genomic typing of both tools shows an optimal concordance level with the gold-standard method, accurately predicting the serotype (both O and H antigens) for 236 out of 282 analyzed isolates. The discordance rate was 12 isolates out of 282. In addition, 34 isolates were correctly typed by the genomic methods, whereas typing with the gold-standard was unsuccessful. Genomic typing was able to classify all isolates while staying as close as possible to the present classification of Salmonella into subspecies and serovars.DiscussionsWhole genome sequencing has proven to be a robust and reliable method for Salmonella typing. It allows for the simultaneous analysis of multiple samples and shortens processing times. Moreover, WGS enabled the recovery of identifications that could not be obtained using the gold-standard method.